Analysis of the Supreme Court Decision on the Calculation of Compensation Based on the Reason for Termination of Employment (Case Study of Supreme Court Decision Number 131 K/Pdt.Sus-PHI/2024) - Agustini Dwi Rahmawati, (Indonesian Journal of Labour Law and Industrial Relations, 2024)
Termination of Employment Relationship means the termination of the employment relationship due to a certain matter that results in the termination of rights and obligations between the worker/laborer and the employer. This marked the beginning of suffering for both the worker and the people who depend on him (his family). Therefore, employers, workers/laborers, trade unions/labor unions, and the government, with all efforts, must make every effort to prevent termination of employment. Termination of Employment can occur for several reasons, including: resignation, worker/laborer's fault or employer's error. In Government Regulation No. 35 of 2021 concerning Certain Time Work Agreements, Outsourcing, Working Time and Rest Time, and Termination of Employment has been regulated regarding compensation in the process of Termination of Employment, the compensation that must be paid in the form of Severance Pay, Service Period Award Money, Replacement Money and wages that must be paid during the Termination of Employment process have not been completed at their level. This study aims to find out whether the Supreme Court Judge's consideration in determining the reason for termination of employment is appropriate and to find out the difference in compensation for termination of employment based on the reason for termination of employment. The research method used in this study is normative juridical. The results of the research related to the determination of the reasons for the termination of employment are appropriate, but in deciding compensation, the Judge did not provide Process Wages. The author provides an opinion that may be the reason why the judge does not compensate for the process wage, that is, there are still often differences in interpretation in his decision to provide the process wage in accordance with the applicable provisions.